The long‐term prognosis of hippocampal neurogenesis and behavioral changes of offspring from rats exposed to valproic acid during pregnancy - Masanobu Ito; Tomoya Kinjo; Tatsunori Seki; Junko Horie; Toshihito Suzuki (Wiley, 2021)
Abstract Aim In pregnant women with epilepsy, it is essential to balance maternal safety and the potential teratogenicity of anticonvulsants. Recently, growing evidence has indicated that valproic acid (VPA) can produce postnatal congenital malformations and impair cognitive function. However, the mechanisms underlying cognitive dysfunction in long‐term prognoses remain unclear. Methods Pregnant Wistar rats received daily intraperitoneal injections of VPA (200 mg/kg/day) from embryonic day 12.5 until birth. On postnatal day (PD) 149, the rats received an injection of bromodeoxyuridine (BrdU). On PD 150, the rats were subjected to the open field (OF), elevated plus‐maze (EPM), and Y‐maze tests. After behavioral testing, perfusion fixation was performed and the brain was dissected for immunohistochemistry. Results A significant marked decrease was seen in the number of BrdU‐positive cells in the dentate gyrus of offspring of VPA‐treated dams compared to those of control. However, no significant differences in hyperactivity were found based on the results of the OF test among the offspring on PD 150 of 200 VPA‐treated dams. In addition, no significant differences were seen in the EPM test. Conclusion The behavioral abnormality observed in young offspring of VPA‐treated dams was not significantly different from that of controls in adult offspring on PD 150. However, compared with controls, the number of BrdU‐positive cells in VPA‐treated rats was halved. The findings suggest that the behavioral abnormality seems to improve as they grow, even if some structural abnormalities may remain in the central nervous system.